2016
DOI: 10.1016/j.otsr.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Medial patellofemoral ligament reconstruction for patellar instability following total knee arthroplasty: A review of 6 cases

Abstract: IV - Retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…There are four main treatment procedures for patellar dislocation after TKA: proximal realignment[ 19 ], medial patellofemoral ligament (MPFL) reconstruction[ 20 - 22 ], distal realignment including tibial tuberosity osteotomy (TTO)[ 23 ], and lateral retinaculum release[ 24 ]. When any procedure is performed, Gennip et al [ 21 ], and Goto et al [ 25 ] suggested that alignment of the implant should be assessed first, to determine whether it is within the normal range of alignment.…”
Section: Discussionmentioning
confidence: 99%
“…There are four main treatment procedures for patellar dislocation after TKA: proximal realignment[ 19 ], medial patellofemoral ligament (MPFL) reconstruction[ 20 - 22 ], distal realignment including tibial tuberosity osteotomy (TTO)[ 23 ], and lateral retinaculum release[ 24 ]. When any procedure is performed, Gennip et al [ 21 ], and Goto et al [ 25 ] suggested that alignment of the implant should be assessed first, to determine whether it is within the normal range of alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published outcomes of MPFLr in this population are limited to small case series or case reports [ 13 , 14 , [29] , [30] , [31] ] ( Table 6 ). In the largest previous series published on this topic, van Gennip et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients experiencing patella instability after arthroplasty are comparatively older and may have poor bone quality [ 11 , 12 ]. Only a small number of studies with low numbers of patients have reported outcomes of patients with PFI after TKA treated using MPFLr [ 13 , 14 ]. Furthermore, the indications for performing MPFLr with or without a tibial tubercle osteotomy (TTO) in a TKA have not been well described previously.…”
Section: Introductionmentioning
confidence: 99%
“…However, among aged populations, cases of total knee arthroplasty (TKA) for knee OA with permanent patellar dislocation [11] or lateral patellar dislocation after TKA are often reported [12, 13]. Accordingly, the authors concluded that the causes of lateral dislocation of the patella after TKA are component malpositions of an anterior, internally rotated, and medial femur; internally rotated tibia; and lateral patella.…”
Section: Discussionmentioning
confidence: 99%